Análisis lingüistico comparativo - Vivanco, Hiram (Revista Chilena de Humanidades, 2016)
Professor Vivanco lays emphasis on the study of proverbs insofar as they reflect expression needs of speakers in human groups, in this case English and Spanish. Sinctacti cal, phonetic, semantic and lexical characteristics come in for analysis as well as others which do not belong in the linguistic field, but that complement it, like those which refer to different kinds of knowledge which are drawn upon through the use of proverbs and their functions. The article concludes with general observations on the nature and practice of proverbs in English and Spanish.